(untitled) (Advances in Military Technology, 2022)
By numerical simulation, influence of the barrel fixing on barrel vibration when a bullet moves down the barrel during shot will be investigated. Both the barrel and bullet were modelled by LS-DYNA software. The barrel is modelled as perfectly straight without any manufacturing deviations. The bullet is a NATO standard 5.56mm calibre consisting of brass jacket and lead core. Gas pressure is applied on the barrel and bullet base. As the bullet is forced into the lands of the barrel, the bullet obtains forward momentum and rotational speed. Interaction of the bullet with the barrel acts as excitation force and the barrel vibrates. In this article, two modifications of the barrels with and without the attachments are shown. These all have an influence on the barrel behaviour during shot mainly at the moment when the bullet leaves the barrel muzzle. Also some impulses are given to the barrel when the bullet leaves the barrel muzzle.